Pengaruh Financial Distress pada Trade Credit Provisions pada Perusahaan Manufaktur di BEI - Darman Saputra; Tubagus Ismail; Nizwan Zukhri (Studi Ilmu Manajemen dan Organisasi, 2024)
Purpose: (IDX) period 2018-2023 by focusing on Financial Distress conditions on Trade Credit Provisions. Financial distress is identified through delisting conditions due to negative net income and book value and inappropriate management decisions. Methodology: Through a quantitative approach with 46 samples of companies selected based on stratified random sampling and purposive sampling methods.Results: The results of the analysis show that there is a significant negative relationship between financial difficulties and accounts payable and there is a significant negative relationship between financial difficulties and accounts receivable in the shares of manufacturing sector companies on the IDX.Conclusions: Based on the results of the analysis that has been carried out on that Financial Distress with each dependent variable Trade Payable and Trade Receivable, namely There is a significant negative relationship between financial difficulties and trade payables in the shares of manufacturing sector companies listed on the Indonesian Stock Exchange and there is a significant negative relationship between financial difficulties and trade receivables in the shares of manufacturing sector companies listed on the Indonesian Stock Exchange.Limitations: The limitations of this research are only on financial distress and manufacturing sector companies 2018-2023Contribution: It is therefore worth considering a deeper exploration of how internal mechanisms, such as working capital management and financing strategies, play a role in determining trade credit policies.